Pengaruh Jenis Kelamin terhadap Penggunaan Gigi Tiruan pada Populasi Lansia: Literature Review - Pamungkas Handy; Anesthesia Pramesti Lasmana Putri (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Introduction: Tooth loss is a common oral health problem in the elderly population and can significantly impact quality of life. The use of dentures is an important solution to restore chewing function, aesthetics, and speaking comfort. This literature review aims to analyze the effect of gender on denture use in the elderly population. Method: The research method uses a narrative review approach by searching various scientific databases such as PubMed, Google Scholar, and Science Direct. Result: Consistent pattern exists that older women have a higher prevalence of denture use than men across countries and research settings. Factors influencing this difference include socioeconomic factors, care-seeking behavior, perceived need, aesthetic considerations, and a higher burden of tooth loss in women. Furthermore, denture use is correlated with improved quality of life and overall health. Women tend to have higher aesthetic expectations and satisfaction, while men are more functionally oriented. Conclusion: Shows that gender is an important factor that needs to be considered in planning dental health services for the elderly population.